A highly active cocatalyst-free semiconductor photocatalyst for visible-light-driven hydrogen evolution: synergistic effect of surface defects and spatial bandgap engineering. Issue 36 (23rd August 2016) - Yu, Guiyang; Zhang, Wenxiang; Sun, Yanjun; Xie, Tengfeng; Ren, Ai-Min; Zhou, Xin; Liu, Gang
Abstract : A synergistic strategy of spatial bandgap engineering and surface defect is efficient to construct a highly active semiconductor photocatalyst. Abstract : Enhancing the efficiency of semiconductor photocatalysts is still a challenging issue for photocatalytic hydrogen evolution. In this work, a synergistic strategy of surface defects and spatial bandgap engineering was realized for constructing a Zn1− x Cd x S/SiO2 photocatalyst. A quantum efficiency of 48.6% (at 420 nm) for hydrogen evolution was obtained without the use of a cocatalyst. The molar ratio of Cd : Zn in Zn1− x Cd x S particles could be gradually tuned from 0.305 : 1 (inside) to 0.490 : 1 (outside). At least a 0.17 eV potential difference is present between the inside and outside of Zn1− x Cd x S particles. Experimental and theoretical analyses showed that photogenerated electrons and holes could vectorially transfer along the spatial bandgap to reach the surface, and be trapped by the surface defects. In situ formed surface Cd species act as the active sites accelerating the surface hydrogen evolution reaction.